2009
DOI: 10.1038/jp.2009.188
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a noise reduction quality improvement project upon sound levels in the open-unit-design neonatal intensive care unit

Abstract: Result: Implementation of a coordinated program of noise reduction strategies did not result in any measurable improvement in levels of loudness or quiet.Conclusion: Two centers, using primarily human behavior noise reduction strategies, were unable to demonstrate measurable improvements in sound levels within the occupied open-unit-design neonatal intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Philbin 15,17 suggested that human behavior change might be necessary, but not sufficient to achieve a quieter NICU environment, and a primarily human behavior strategy, within an OU NICU, to decrease sound levels, was found to be ineffective. Stevens 16 demonstrated the acoustic benefits of SFR design in the unoccupied NICU.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Philbin 15,17 suggested that human behavior change might be necessary, but not sufficient to achieve a quieter NICU environment, and a primarily human behavior strategy, within an OU NICU, to decrease sound levels, was found to be ineffective. Stevens 16 demonstrated the acoustic benefits of SFR design in the unoccupied NICU.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of common NICU equipment is a noise variable that may remain significant despite the above improvements. [15][16][17] Our goal was to compare sound level measurements within an OU level 3 NICU with the SFR level 3 NICU, accounting for the use of common NICU equipment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations